Effect of influent COD/SO42− ratios on UASB treatment of a synthetic sulfate-containing wastewater. (July 2015) - Hu, Yong; Jing, Zhaoqian; Sudo, Yuta; Niu, Qigui; Du, Jingru; Wu, Jiang; Li, Yu-You
Highlights: UASB performance was investigated at COD/SO4 2− ratio ranging from 0.5 to 20. MPA out-competed SRB in COD and electrons utilization at COD/SO4 2− ratios applied. All the SRB species were found to be incomplete oxidizers. Degradation pathways at different COD/SO4 2− ratios were identified. Abstract: The effect of the chemical oxygen demand/sulfate (COD/SO4 2− ) ratio on the anaerobic treatment of synthetic chemical wastewater containing acetate, ethanol, and sulfate, was investigated using a UASB reactor. The experimental results show that at a COD/SO4 2− ratio of 20 and a COD loading rate of 25.2 gCOD L −1 d −1, a COD removal of as high as 87.8% was maintained. At a COD/SO4 2− ratio of 0.5 (sulfate concentration 6000 mg L −1 ), however, the COD removal was 79.2% and the methane yield was 0.20 LCH4 gCOD −1 . The conversion of influent COD to methane dropped from 80.5% to 54.4% as the COD/SO4 2− ratio decreased from 20 to 0.5. At all the COD/SO4 2− ratios applied, over 79.4% of the total electron flow was utilized by methane-producing archaea (MPA), indicating that methane fermentation was the predominant reaction. The majority of the methane was produced by acetoclastic MPA at high COD/SO4 2− ratios and both acetoclastic and hydrogenthrophic MPA at low COD/SO4 2− ratios. Only at low COD/SO4 2− ratios were SRB species such as Desulfovibrio found to play a key role in ethanol degradation, whereas all the SRB species were found to be incomplete oxidizers at both high and low COD/SO4 2− ratios.